A Resonating B, N Covalent Bond and Coordination Bond in Aromatic Compounds and Conjugated Polymers. (8th July 2022) - Shao, Xingxin; Liu, Mengyu; Liu, Jun; Wang, Lixiang
Abstract: We herein report an organoboron compound (SBN‐1 ) based on N−B←N units with a balanced resonance hybrid of B, N single bond (B−N) and B, N coordination bond (B←N). Despite the different chemical environments of the two nitrogen atoms in the N−B←N unit, the single‐crystal structure reveals that the two B, N bonds have similar bond lengths of ca. 1.55 Å and are almost equivalent. The resonance nature of the two B, N bonds contributes to the excellent chemical stability and photostability of SBN‐1 . The N−B←N units in SBN‐1 show a strong electron‐withdrawing capability and large dipole, resulting in a red‐shifted absorption spectrum, downshifted LUMO/HOMO energy levels, and drastically altered molecular packing behaviors in solid state. SBN‐1 can be used as a building block to construct small band gap conjugated polymers. The resonance of B, N bonds discovered in this work provides new insight into the design of stable organoboron small molecules and polymers for practical applications. Abstract : A compound with a resonance hybrid of B, N single and coordination bonds is reported. The organoboron compound is very stable and shows a narrow band gap. The effect of a resonant N−B←N moiety on opto‐electronic properties and the molecular packing behavior of the compound is disclosed.